2022
DOI: 10.1007/s12210-022-01127-z
|View full text |Cite
|
Sign up to set email alerts
|

Is there a link between the length of the solar cycle and Earth’s temperature?

Abstract: The Sun provides most of external energy to Earth’s system and thus has the potential of influencing it. Various studies reported a correlation between the solar cycle length and the northern hemisphere temperatures on Earth. Here, we reassess the cycle length record by incorporating the newly revised and updated sunspot number series as well as plage area composite, before comparing it to Earth temperature records. We find that cycle length series constructed from sunspot and plage data exhibit the same behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 78 publications
(111 reference statements)
0
7
0
1
Order By: Relevance
“…At the team meetings, Pesnell represented the space-forecasting community, Van Driel-Gesztelyi served as rapporteur, and Kopp reviewed the "triad" results (see below) and mapped the path forward. This also led to considerations about the broader implications of the current upgrades of the long-term sunspot series, which go beyond the domain of solar physics (e.g., Chatzistergos, 2022).…”
Section: Summary Of Progressmentioning
confidence: 99%
“…At the team meetings, Pesnell represented the space-forecasting community, Van Driel-Gesztelyi served as rapporteur, and Kopp reviewed the "triad" results (see below) and mapped the path forward. This also led to considerations about the broader implications of the current upgrades of the long-term sunspot series, which go beyond the domain of solar physics (e.g., Chatzistergos, 2022).…”
Section: Summary Of Progressmentioning
confidence: 99%
“…Three of these studies agreed with C2021 that: (a) much of the long-term warming since the late 19th century could be explained in terms of changing solar activity and (b) the IPCC had substantially underestimated the solar contribution [17,18,22]. Two of the studies disagreed with C2021 and concluded that the solar contribution was very small [20,21]. The remaining study reached an intermediate conclusion, finding that TSI was the dominant climate driver up to 1960 but that afterward CO 2 appeared to dominate [19].…”
Section: Influence Of C2021's Findings On Recent Attribution Studiesmentioning
confidence: 80%
“…Therefore, the concerns raised by C2021 were apparently not considered for AR6's attribution statement. Nonetheless, a number of recent global temperature attribution studies have explicitly considered different aspects of C2021 in their analysis [17][18][19][20][21][22].…”
Section: Influence Of C2021's Findings On Recent Attribution Studiesmentioning
confidence: 99%
See 2 more Smart Citations